INNOVATIVE PEDAGOGICAL TECHNOLOGIES IN THE MODERN EDUCATIONAL SYSTEM - Akhmedov B.A. (Scholar Express Journal, 2023)
The article considers innovative activity in education as a socially significant practice aimed at the moral self-improvement of a person, which is capable of transforming all existing types of practices in society
Keywords: innovative technologies; innovative approach to education; pedagogical innovation